Composite materials for multimodal sonodynamic therapy in biomedical applications - Min Ma; Lili Luo; Yuxuan Ding; Jiayi Zuo; Xiaofen Chai; Libing Liu (Next Materials, 2025)
Sonodynamic therapy (SDT) presents significant advantages, such as improved tissue penetration, non-invasiveness, and reduced susceptibility to drug resistance, positioning it as a promising modality in the biomedical domain. Recent advancements in the structural modification and component optimization of sonosensitizers have markedly enhanced the efficacy of SDT, especially in the production of reactive oxygen species (ROS). Additionally, sonosensitizers can be engineered into functional particles through various methodologies, thereby achieving enhanced biocompatibility and catalytic efficiency. This review concentrates on recent advancements in sonosensitizers, with a particular emphasis on piezoelectric materials and conjugated polymers (CPs). These innovations have shown promise in the treatment of pathogenic microbial infections, the targeting of cancer cells, and the enhancement of 3D bioprinting techniques for wound repair. Furthermore, the review discusses the primary challenges and prospective future directions for the biomedical applications of these materials.